OF WORK TO WELFARE? WORKERS OF “TUCSON HATS”, MEXICO - Valerdi González, María Áurea (2014)
In this article is presented the first results of an investigation about the hat industry workersand their welfare, in San Francisco del Rincon, Guanajuato, Mexico. The approachof the research is focused on the relationship between macro living conditions (housing,health, education and income) and micro work issues such as personal satisfaction andstrategies of employees to be placed in a less disadvantaged.